PTH-101 A manualised intervention to reduce psychological distress in inflammatory bowel disease: a pilot randomised controlled feasibility trial. (17th June 2017) - Hughes, LD; Fischer, A; Goodliffe, S; Irving, PM; Moss-Morris, R
Abstract : Introduction: Depression and anxiety are common problems in inflammatory bowel diseases (IBD). In part due to its cost, the availability of psychological intervention for IBD patients is low. To address this, a novel IBD specific self-management manual (Quality of Life Tool for IBD - QOLITI) was developed. This was piloted with minimal therapist support. The aim of this pilot trial was to measure the feasibility and acceptability of a primarily self-administered intervention targeting IBD-related distress. Method: A two-arm randomised control trial (NCT02707068 ) was conducted. Patients with a diagnosis of IBD were recruited from hospital clinics and online through the Crohn's and Colitis UK website. Patients were randomised into either the intervention arm (n=32) or waitlist control arm (n=31). Validated questionnaire measures were administered pre and post intervention (8 weeks). The intervention arm received QOLITI, task book and three telephone support sessions. Following intervention completion, participants in the treatment arm were invited to participate in semi-structured interviews to provide feedback on the QOLITI. Results: The mean age of the treatment group was 38 (SD=11.9) years, 59% were female, 59% had Crohn's Disease and the mean years since diagnosis was 12.2 (SD=12.8). The mean age of the control group was 43 (SD=13.7) years, 66% were female, 50% had Crohn's Disease and the mean years since diagnosis was 10.7 (SD=7.7). Randomisation checks indicated that participants did not differ between groups. 97% of patients approached in clinics were eligible and 50% subsequently consented. 85% of patients who began the trial were retained in the study. 80% of those in the treatment arm completed at least 1 telephone session. Semi-structured interviews with 11 participants indicated a high level of acceptability with willingness to actively engage with the manual, despite challenging tasks. The manual was generally perceived as useful with some participants reporting changing their behaviour and/or thoughts about IBD as a direct result of the tasks performed. Conclusion: Good feasibility and acceptability was shown for a self-directed manual targeting distress. It is feasible to recruit participants from clinics and retain them through an 8 week intervention. Telephone support was helpful to guide progress through the manual. Feedback on the manual was positive and further testing following MRC guidelines will continue to test the effectiveness, cost-effectiveness and implementation of the QOLITI. Disclosure of Interest: None Declared